L’aborto di fronte alla filosofia - Pascual LC, Fernando (Alpha Omega, 2010)
Abortion must be considered with the aid of philosophy: from a metaphysical, anthropological and ethical point of view. This article attempts to show some of the principal areas in the relationship between abortion and philosophy following four movements. The problem is presented (I), then Plato’s and Aristotle’s attitude with regard to abortion are analysed (II). Nextly there follows a synthetic overview of modern thought on the subject (III) and some bioethical solutions that have deep philosophical roots are proposed (IV). Finally the article stresses the importance of philosophical reflection in order to guarantee the maximum respect possible for the unborn (V).